HIGHER EDUCATION INSTITUTIONS AS STRATEGIC PARTNERS' IN BRIDGING PUBLIC SECTOR INFORMATION SECURITY GAPS: THE UGANDAN CONTEXT (African Journal of Public Administration & Management, 2026)
Information security is commonly described through keyattributes that guide the protection of digital & physicalinformation.CIA Triad model:Confidentiality so accessibility only to authorised individualsIntegrity ensures accuracy, completeness and reliability of informationAvailability – authorised users can access information and systems when required.
Keywords: PUBLIC SECTOR INFORMATION SECURITY; HIGHER EDUCATION INSTITUTIONS; RATEGIC PARTNERS